The role of adipokines in osteoporosis management: a mini review - Patil, Jayaditya Devpal; Fredericks, Salim (Frontiers in Endocrinology, 2024)
The prevalence of osteoporosis has been on the rise globally. With ageing populations, research has sought therapeutic solutions in novel areas. One such area is that of the adipokines. Current literature points to an important role for chemical mediators in bone metabolism. Well established adipokines, such as adiponectin and leptin, have been broadly reported upon. However, other novel adipokines such as visfatin, nesfatin-1, meteorin-like protein (Metrnl), apelin and lipocalin-2 are starting to be addressed pre-clinically and clinically. Adipokines hold both pro- and anti-inflammatory properties that mediate the pathophysiology of various bone diseases. Omentin-1 and vaspin, two novel adipokines, share cardioprotective effects and play essential roles in bone metabolism. Some studies have reported protective effects of omentin-1 on bone health, whilst others report negative associations between omentin-1 and bone mineral density. Lipocalin-2 is associated with poor bone microarchitecture in mice and is even suggested to mediate osteoporosis development from prolonged disuse. Nesfatin-1, an anorexigenic adipokine, has been known to preserve bone density. One animal study has even concluded nesfatin-1 treatment limits bone loss and increases bone strength, suggesting exogenous use as a potential treatment for osteopenic disorders. Pre-clinical studies have shown adipokine apelin to have a role in bone metabolism by enhancing osteoblast genesis and inhibiting apoptosis. Although many studies report conflicting findings, sufficient literature supports the role of adipokines in bone metabolism. This review aims to highlight the role of novel adipokines in osteoporosis while also discussing their potential for treating osteoporosis.